P–TNM staging system for colon cancer: combination of P-stage and AJCC TNM staging system for improving prognostic prediction and clinical management - Liu Q (Cancer Management and Research, 2018)
Qi Liu,1,2 Dakui Luo,1,2 Sanjun Cai,1,2 Qingguo Li,1,2 Xinxiang Li1,2 1Department of Colorectal Surgery, Fudan University Shanghai Cancer Center, Shanghai, People’s Republic of China; 2Department of Oncology, Shanghai Medical College, Fudan University, Shanghai, People’s Republic of China Aim: This study focused on improving the American Joint Committee on Cancer TNM staging system and demonstrated an improvement in prognostic accuracy and clinical management of colon cancer using the P–TNM staging system. Patients and methods: Eligible patients (N=56,800) were identified from the Surveillance, Epidemiology, and End Results database between January 1, 2010, and December 31, 2014. The P-stage (P0 or P1) was assigned to each patient based on age at diagnosis, tumor grade, and tumor size. The outcome of interest was cancer-specific survival (CSS). The Cox proportional hazards regression analyses were used to identify independent prognostic factors and analyze the CSS probabilities of patients with colon cancer having different P–TNM stages, respectively. Results: A total of 29,627 patients were assigned to P0-stage and 27,173 patients were assigned to P1-stage. The P1-stage was associated with a 98.1% increased risk of cancer-specific mortality (hazard ratio =1.981, 95% confidence interval =1.891–2.076, P<0.001), which was higher in patients with nonmetastatic colon cancer. The P1-stage patients had improvement in CSS compared with those in P0-stage in respective stages (P<0.001). Moreover, CSS decreased in stage I–P1 compared with stage IIA–P0 or IIIA–P0 (P<0.001), stage IIIA–P1 compared with stage IIA–P0 (P<0.001), stage IIB–P1 compared with stage IIIB–P0 or IIC–P0 (P<0.001), stage IIIB–P1 compared with stage IIC–P0 (P<0.001), and stage IIC–P1 compared with stage IIIC–P0 (P<0.001). Conclusion: P-stage was an independent prognostic factor for colon cancer. This study strongly supported the incorporation of P-stage into the American Joint Committee on Cancer TNM staging system for a better approach to prognostication and, thus, more individualized risk-adaptive therapies in colon cancer. Keywords: prognostic score, colon cancer, AJCC TNM staging system